On studying those who study abroad: Insights into Early Career Migrant Researchers’ subjectivities within the Western European University - Angelichin-Zhura, Gordana; Erismann, Annelise (Journal of International Students, 2023)
With the global as the dominating frame of reference, the international higher education landscape and its transients move to the forefront of discussions on whose and which education matters today. Embodying the internationalized university, the Global Southern international student turned into an early-career migrant researcher remains a valuable access point to consent and dissent from Western cultural hegemony at the European neoliberal university. Using Pitard’s term (2017) for reflexivity in qualitative research, this paper reflects on an “internal dialogue” of two women PhDs, one from North Macedonia and one from Brazil, studying international student mobility in continental Europe. From the position of “host-sponsored international students who study international students,” we discuss the ambiguity of embodying power and subservience. We conclude that the reflexivity demonstrated here, especially in South-South solidarity constellations, has the potential to reignite debates on global knowledge production today.